2013
DOI: 10.1109/wcl.2013.13.120778
|View full text |Cite
|
Sign up to set email alerts
|

Performance of SC Receiver over TWDP Fading Channels

Abstract: Performance of selection combining (SC) receiver has been derived over two-wave diffused power (TWDP) fading channels with arbitrary and non-identical fading parameters. An expression of cumulative distribution function (CDF) of signalto-noise ratio (SNR) for TWDP fading channel has been derived, which is used to obtain the probability density function (PDF) of SNR at the output of SC receiver. The PDF of output SNR has been used to derive expressions of outage probability and average bit error rate for cohere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The threshold value is set at 3dB. It is observed that for a constant value of M=2, the performance improves with the increase in the number of SC branches, L. This is due to the fact that as the number of diversity branches increases, the probability of all the fading paths going to deep fade decreases [13]. Similar observation is found in the case with dual SC hybrid receiver.…”
Section: Numerical Results and Discussionsupporting
confidence: 52%
“…The threshold value is set at 3dB. It is observed that for a constant value of M=2, the performance improves with the increase in the number of SC branches, L. This is due to the fact that as the number of diversity branches increases, the probability of all the fading paths going to deep fade decreases [13]. Similar observation is found in the case with dual SC hybrid receiver.…”
Section: Numerical Results and Discussionsupporting
confidence: 52%
“…Given the PDF of the envelope over a TWDP fading channel in (6) and that γ =γ/2σ 2 (K + 1), the corresponding PDF of the SNR can be obtained by performing a squared transformation of the random variable r, in (6) [20]. Formally,…”
Section: B Twdp Fading Modelmentioning
confidence: 99%
“…Second, the relative strength of the two specular waves is expressed as ∆ = 2V 1 V 2 /(V 2 1 + V 2 2 ). According to [7], the probability density function (PDF) of the signal-to-noise ratio (SNR) over a TWDP channel is expressed as,…”
Section: Spectrum Sensing Over Twdp Fading Channelsmentioning
confidence: 99%